SOCIAL ENTREPRENEURIAL INTENTIONS AND MOTIVATIONAL DRIVERS AMONG BUSINESS STUDENTS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The paper is aimed at determining young people's motives and views related to entrepreneurship, in particular social entrepreneurship. To this purpose, a survey was conducted at the School of Economics and Business in Sarajevo to explore the motivations of the student population to pursue entrepreneurship, with a focus on social entrepreneurship and their intentions to engage in it. The survey examined socio-political, situational and personal factors and their direct and mediating effect on the intention to engage in social entrepreneurship.Methodology: The research model and methodology presented in the paper are based on the process theory of motivation and the model used by Barton et al. (2018) and by Krueger (1993).  The model elaborated by this paper’s authors is expanded and redefined so as to take account of socio-political factors and the respondents’ views of them.Results: The research revealed a limiting and de-stimulating effect of environmental factors on the intention to start a business, as well as the significance of situational and personal factors when deciding on engaging in social entrepreneurship.Conclusion: The conducted research revealed that young people in Bosnia and Herzegovina understand the significance of social entrepreneurship for society at large, as well as for themselves, i.e. the sense of fulfilment it could bring. The results could suggest that, for the respondents, the desirable entrepreneurial option would be the one that implies involvement not in the social entrepreneurship but in the socially responsible entrepreneurship.